2003
DOI: 10.1126/science.1077771
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ1 Gain-of-Function Mutation in Familial Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is a common cardiac arrhythmia whose molecular etiology is poorly understood. We studied a family with hereditary persistent AF and identified the causative mutation (S140G) in the KCNQ1 (KvLQT1) gene on chromosome 11p15.5. The KCNQ1 gene encodes the pore-forming alpha subunit of the cardiac I(Ks) channel (KCNQ1/KCNE1), the KCNQ1/KCNE2 and the KCNQ1/KCNE3 potassium channels. Functional analysis of the S140G mutant revealed a gain-of-function effect on the KCNQ1/KCNE1 and the KCNQ1/KCNE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
383
0
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 899 publications
(399 citation statements)
references
References 21 publications
6
383
0
10
Order By: Relevance
“…Previous studies reported that KCNQ1 mutations were associated with long QT syndrome [8] and familial atrial fibrillation [9]. GWA scans have recently linked KCNQ1 to susceptibility to type 2 diabetes in a Japanese population [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that KCNQ1 mutations were associated with long QT syndrome [8] and familial atrial fibrillation [9]. GWA scans have recently linked KCNQ1 to susceptibility to type 2 diabetes in a Japanese population [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…In the other 11 investigated genes, no more mutations were identified in the 120 probands, except those that were reported earlier. 12,17,21 Multiple alignment of the Kv1.5 protein sequences across species A cross-species alignment of Kv1.5 protein sequences showed that the altered amino acids, except for Ala576, are completely conserved evolutionarily (Figure 3). in the net outward current compared with that generated by the expression of wild-type KCNA5 alone (Figure 4).…”
Section: Kcna5 Mutations In Af Kindreds and Patients With Idiopathic Afmentioning
confidence: 99%
“…Specific variations in several genes associated with AF were identified and characterized. These AF-related genes are mainly as follows: KCNQ1, which encodes the a-subunit of slowly activating delayed rectifier potassium channel (IKs); 12 HERG, which encodes the a-subunit of the rapidly activating delayed rectifier potassium channel (IKr); 13 SCN5A, which encodes the a-subunit of the sodium channel; 14,15 Ankyrin-B, which encodes a member of a family of versatile membrane adapters, which is required for coordinated assembly of the Na/Ca exchanger, Na/K ATPase and inositol trisphosphate receptor at transverse tubule/sarcoplasmic reticulum sites in cardiomyocytes; 16 KCNJ2, which encodes the a-subunit of inward rectifier potassium channel (IK1); 17 KCNA5, which encodes the a-subunit of the ultrarapidly activating delayed rectifier potassium channel (Kv1.5); 18 Connexin 40, which is expressed selectively in atrial myocytes and mediates the coordinated electrical activation of the atria; 19 KCNE1, which encodes the b-subunit of IKs; 20 KCNE2 encoding b-subunit of IKr; 21 and KCNE3, 22 KCNE4 23 and KCNE5, 24 which encode the b-subunits of potassium channels interacting with KCNQ1, HERG and others. In addition, inheritable defects also confer substantial disease susceptibility on patients with secondary AF.…”
Section: Introductionmentioning
confidence: 99%
“…38 However, atrial fibrillation as well as inducible ventricular fibrillation have been observed in several European families with QTc Յ 260 milliseconds, characteristics of the short QT syndrome. 39 Reports are emerging of further possible associations with the LQT1, 2, and 7 genotypes.…”
Section: Long Qt Syndrome Huge Reviewmentioning
confidence: 99%